Safety in Cities and Transport through Sound Monitoring - Smazinka, Dalibor; Hrinko, Martin (Communications - Scientific Letters of the University of Zilina, 2022)
This paper deals with the use of modern technology for security purposes, focusing on the situation in cities (urban noise and shooting) and in transport (passenger rail). The authors aimed to highlight the possibilities and capabilities of installation of technology in the field of applied physical acoustics (sensors, evaluation system with the possibility of setting sensitive sensing filters, end output) and the possibilities of monitoring, including the response of security forces or security measures to the detected danger. In the paper, the authors also include graphical representations of the energy-normalized spectra of the different sound backgrounds and classification classes of acoustic events and types of acoustic events to clarify the differences of the selected monitored events.
Keywords: urban safety; traffic safety; sound events; sound classification; video surveillance; audio surveillance; safety system response